2015
DOI: 10.1001/jamapediatrics.2014.3577
|View full text |Cite
|
Sign up to set email alerts
|

Teen Dating Violence (Physical and Sexual) Among US High School Students

Abstract: IMPORTANCE National estimates of teen dating violence (TDV) reveal high rates of victimization among high school populations. The Centers for Disease Control and Prevention’s national Youth Risk Behavior Survey has provided often-cited estimates of physical TDV since 1999. In 2013, revisions were made to the physical TDV question to capture more serious forms of physical TDV and to screen out students who did not date. An additional question was added to assess sexual TDV. OBJECTIVES To describe the content … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
200
4
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 293 publications
(223 citation statements)
references
References 33 publications
13
200
4
6
Order By: Relevance
“…Content could be included and embedded within foundational and practice courses covering curricula specific to the developmental period of adolescence (e.g., HBSE) and with practice vignettes such as those used in this study in order to assess practice competencies. Given the high prevalence of teen dating violence (Vagi et al, 2015), it is likely that social workers will come across this issue; it is important to prepare them to handle it effectively.…”
Section: Resultsmentioning
confidence: 99%
“…Content could be included and embedded within foundational and practice courses covering curricula specific to the developmental period of adolescence (e.g., HBSE) and with practice vignettes such as those used in this study in order to assess practice competencies. Given the high prevalence of teen dating violence (Vagi et al, 2015), it is likely that social workers will come across this issue; it is important to prepare them to handle it effectively.…”
Section: Resultsmentioning
confidence: 99%
“…It indicated that mean age 16.8 (14-22 years) of smoking, 17.9 (15-22 years) of alcohol drinking, 15.3 (13-22 years) of sexual relationship (Table 3 and Table 4). Several studies found that the youth risk behaviors leading to traf ic accidents were rare (13)(14)(15)(16)(17)(18)(19)(20)(21)(22) or never having worn seat belt or helmet while motorcycling, riding with who had consumed alcohol and driving after consuming alcohol and had sexual intercourse with never using condom, smoking, carrying weapon and had been involved in violent event [15,11,10] . Moreover, younger people had more new smokers and drinkers (Department of Health [3], at least 1 in 10 younger adolescents use tobacco [15].…”
Section: Resultsmentioning
confidence: 99%
“…Por ende, la prevalencia de este fenómeno ha llegado a sugerir un problema de salud social (Vagi, O Malley, Basile y Vivolo-Kantor, 2015), sin embargo aún son escasas las investigaciones al respecto (Barrachina, Castro y Giménez, 2017;Dick et al, 2015;Frías y Finkelhor, 2017;Korchmaros, Ybarra, Langhinrichsen-Rohling, Boyd y Lenhart, 2013). Una situación que predomina en el contexto académico mexicano donde se pueden destacar los estudios de Lucio-López y Prieto-Quezada (2011) o Martínez-Lanz et al (2016) quienes hallaron indicios de la existencia de ciber-violencia hacia la pareja en jóvenes mexicanos.…”
Section: La Teoría Del Apego Y Las Relaciones De Pareja En Adolescentesunclassified